Root decomposition in silvopastures is influenced by grazing, fertility, and grass species. Issue 3 (12th July 2021) - Ashworth, Amanda J.; Adams, Taylor; Kharel, Tulsi; Philipp, Dirk; Owens, Phillip; Sauer, Thomas
Abstract: Grass root production and decomposition is a major source of C entering soils, although rates are largely unknown based on edaphic and management factors. Therefore, study objectives were to evaluate four explanatory variables including forage species (native and nonnative), fertility (poultry litter and a control), soil moisture (udic and aquic), and pasture management (grazed and an ungrazed control) in order to evaluate driving factors for root turnover and subsequent soil organic matter formation in silvopastoral systems using the root litter bag technique. Native grass root decomposition was accelerated relative to the nonnative forage based on root mass balance, as well as the exponential decay function, likely owing to greater five‐ and six‐C sugars and more digestible root tissues of native grasses. These physiochemical results suggest more favorable microbial food sources, which culminate in faster decomposition and greater microbially derived organic matter. Overall, there was greater root sloughing and subsequent soil organic matter formation potential with native grass species and poultry litter applications, with soil moisture affecting decomposition to a lesser extent. This study contributes to the understanding of complex interactions of grass species, soil moisture, nutrients, and grazing, which controls primary productivity, as well as nutrient cycling and C sequestration in silvopastures. Core Ideas: Root decomposition is a major source of C entering soils in grasslands. Native grass roots decomposed quicker than roots from the nonnative forage. Poultry litter increased root decay, with soil moisture affecting rates to a lesser extent. Root chemical composition and management were driving factors for decomposition. This work contributes to understanding factors affecting root decomposition.